ANALISIS KEPASTIAN HUKUM PEKERJA DALAM PERJANJIAN KERJA LISAN UNTUK MENJAMIN HAK DAN KESEJAHTERAAN DI INDONESIA - Muhammad Tunjang Syaeh; Nayla Hishah Novianti; Najwa Syifa Aulia (Jurnal Hukum Statuta, 2026)
The dominance of informal sector workers in Indonesia has led to many employment relationships being based on oral agreements, which raises issues of legal certainty also protection of workers’ rights, particularly in evidentiary process of industrial relations disputes. Normatively, oral agreements are recognized under Article 50 and Article 51 paragraph (1) of Law Number 6 of 2023 concerning Job Creation, as long as they fulfill elements of work, wages, also orders; however, in practice, they have not provided optimal protection. Employs normative juridical method with statutory also conceptual approaches. Indicate absence of written evidence weakens workers’ positions and increases the risk of violations of normative rights, such as wages, working hours, social security, and protection against unilateral termination. Although regulated under Article 57 paragraph (1) and Article 88 paragraph (1) of the Job Creation Law, as well as supported by Government Regulation Number 35 of 2021 and Number 36 of 2021, their implementation remains suboptimal. Strengthening role of the state is necessary throughout preventive mechanisms, such as employment relationship registration and enhanced supervision, to ensure legal certainty as well as protection and welfare of workers. Keywords: Oral Agreement, Legal Protection, Legal Certainty.